2010
DOI: 10.1103/physrevlett.104.125302
|View full text |Cite
|
Sign up to set email alerts
|

Supersolid Phase with Cold Polar Molecules on a Triangular Lattice

Abstract: We study a system of heteronuclear molecules on a triangular lattice and analyze the potential of this system for the experimental realization of a supersolid phase. The ground state phase diagram contains superfluid, solid and supersolid phases. At finite temperatures and strong interactions there is an additional emulsion region, in contrast to similar models with short-range interactions. We derive the maximal critical temperature Tc and the corresponding entropy S/N = 0.04(1) for supersolidity and find fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
180
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 36 publications
7
180
1
1
Order By: Relevance
“…Thus, experiments with polar molecules go beyond quantum simulation of effective theories motivated by electronic systems and aim at exploring a genuinely new domain of many-body quantum behavior, unique to dipolar interactions. Dipolar interactions can be utilized to generate long-range interactions of arbitrary shape using microwave fields [11], simulate exotic spin Hamiltonians [12,13] and are theoretically predicted to give rise to numerous interesting collective phenomena such as roton softening [14][15][16], supersolidity [17][18][19][20][21], p-wave superfluidity [22], emergence of artificial photons [23], bilayer quantum phase transitions [24], multi-layer self-assembled chains [25] for bosonic molecules, dimerization and inter-layer pairing [26,27], spontaneous inter-layer coherence [28], itinerant ferroelectricity [29], anisotropic Fermi liquid theory and anisotropic sound modes [30][31][32][33], fractional quantum Hall effect [34], Wigner crystallization [35], density-wave and striped order [36,37], biaxial nematic phase [38], topological superfluidity [39] and Z 2 topological phase [40], just to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, experiments with polar molecules go beyond quantum simulation of effective theories motivated by electronic systems and aim at exploring a genuinely new domain of many-body quantum behavior, unique to dipolar interactions. Dipolar interactions can be utilized to generate long-range interactions of arbitrary shape using microwave fields [11], simulate exotic spin Hamiltonians [12,13] and are theoretically predicted to give rise to numerous interesting collective phenomena such as roton softening [14][15][16], supersolidity [17][18][19][20][21], p-wave superfluidity [22], emergence of artificial photons [23], bilayer quantum phase transitions [24], multi-layer self-assembled chains [25] for bosonic molecules, dimerization and inter-layer pairing [26,27], spontaneous inter-layer coherence [28], itinerant ferroelectricity [29], anisotropic Fermi liquid theory and anisotropic sound modes [30][31][32][33], fractional quantum Hall effect [34], Wigner crystallization [35], density-wave and striped order [36,37], biaxial nematic phase [38], topological superfluidity [39] and Z 2 topological phase [40], just to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…[95] with highly magnetic atoms. Dipolar interactions modify the traditional Hubbard model and can lead to novel phases including supersolid and stripe phases [96,97,98]. In bulk gases of bosonic magnetic atoms, the competition between contact and dipolar interactions has led to the observation of droplets, which are stabilized by quantum fluctuations [99,100].…”
mentioning
confidence: 99%
“…Here, between a superfluid and a crystal phase, Pollet et al [13] identified a supersolid phase as well as a microemulsion as proposed in Ref. [26].…”
Section: Model Hamiltonian and Methodologymentioning
confidence: 99%
“…Concerning a quantum regime, recent studies have pointed out that the supersolid phase can be observed in optical lattices [8,11,12,13]. For example, Pollet et al [13] have studied a complete phase diagram of a two-dimensional system composed of cold polar molecules on a triangular lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation